Middle leaders as teacher educators: The case of the Kenkyushunin (chief teacher of school research) in Japan - Yonezawa, Takashi; Watanabe, Takumi; Yamasaki, Akane (Frontiers in Education, 2023)
Currently, Japan needs to create a framework that facilitates improving teachers’ professional development—a situation in which teacher educators become vital. This study focuses on the role of the kenkyushunin (chief teacher of school research) in the professional development of in-service teachers through school-based training, lesson studies, peer mentorship, and student guidance. Extant literature was analyzed to enable an in-depth understanding of their role. The findings indicated that the roles of a kenkyushunin as a teacher educator could be categorized as that of a teacher of teachers, researcher, coach, curriculum developer, and a broker. However, their role as a gatekeeper could not be confirmed. Further, their behaviors in each of these roles were also discussed. It was found that, as a school-based teacher educator, the kenkyushunin conducts lesson studies and joint research relating to the practice of teaching with colleagues and undertakes the professional development of teachers.